The Legal Protection Against Children Who Did Criminal Actions Through Diversion - Masngud Afandi; Gunarto Gunarto (Universitas Islam Sultan Agung, 2021)
The purpose of this study is to examine and analyze the legal protection of children who commit crimes through diversion in terms of the juvenile criminal justice system. This study uses a normative juridical approach. Based on the research, it is concluded that children dealing with the law are considered as legal subjects who are not yet competent and cannot understand what they are doing. Investigation of children's cases is carried out by investigators determined by the Decree of the Head of the State Police of the Republic of Indonesia or other officials appointed by the Head of the State Police of the Republic of Indonesia. On the other hand, if the Diversion process fails, the Investigator is obliged to continue the investigation and delegate the case to the Public Prosecutor by attaching the diversion report and the community research report. Arrested children must be deposited in LPKS. The cost for each child placed in LPKS is charged to the budget of the ministry that carries out government affairs in the social sector.